Forest inventory by compartments using satellite imagery. - Poso, Simo; Paananen, Raito; Similä, Markku (Silva Fennica, 1987)
A method for using satellite data in forest inventories and updating is described and tested. The stand characteristics estimated by the method showed high correlation with the same characteristics measured in the field. The correlation coefficients for volume, age and mean height were about 0.85. It seems that the method is applicable to practical forestry. Extensive work in programming, however, is required. The PDF includes an abstract in Finnish.